STUDY ON INFLUENCE OF PROCESSING TECHNOLOGY TO RESIDUAL STRESS FOR AERONAUTICAL PMMA BY PHOTOELASTICITY - SHANG Wei; YANG XiaoJing; ZHANG LiNa (Jixie qiangdu)
The damage of the aeronautical PMMA is mainly due to the fatigue cracking leaded by the residual stress.Residual stress will produce the orientated segment or group in the aeronautical PMMA which produce the birefringence effect. In this paper,based on the birefringence effect,the digital phase-shift photoelasticity is used to test the residual stress for drilling the hole. For the test results some conclusions are summarized. When the feed speed is smaller,for the longer processing time the larger residual stress is frozen. When the rotational speed is greater,for the higher processing temperature the larger residual stress is frozen. Though controlling the chucking the constraints are the same in all directions. This can make the residual stress uniform and prevent the large stress concentration area. As machining the larger hole the smaller hole should be drilled firstly.This can ensure the smaller residual stress around the hole.